2007
DOI: 10.1038/sj.jhh.1002195
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of heart-type fatty acid-binding protein for left ventricular remodelling and clinical outcome of hypertensive patients with mild-to-moderate aortic valve diseases

Abstract: Heart-type fatty acid-binding protein (H-FABP), a marker of acute myocardial infarction and a soluble cytosolic protein, may be released following left ventricular remodelling in cardiac overloaded hearts caused by hypertension, aortic regurgitation (AR) or aortic stenosis (AS). Our aim was to investigate if H-FABP levels are associated with left ventricular remodelling and clinical outcome in hypertensive patients with AR or AS. H-FABP and brain natriuretic peptide (BNP) were measured, glomerular filtration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Considering patients with valvular heart disease, Iida et al showed an independent association of H-FABP with clinical outcomes in hypertensive patients with aortic valve disease. Echocardiographically determined left ventricular dimensions were signs of cardiac remodelling and correlated significantly with measured levels of H-FABP, whereas Troponin T remained below cut-off levels in all patients [21]. Mirna et al actually reported a significant reduction in H-FABP plasma concentration in 79 patients with severe aortic valve stenosis after conducting transcatheter aortic valve implantation (TAVI), indicating reduced ventricular wall stress and potential reversibility of cardiac remodeling due to valvular replacement [69].…”
Section: H-fabp As a Biomarker In Heart Failurementioning
confidence: 97%
See 2 more Smart Citations
“…Considering patients with valvular heart disease, Iida et al showed an independent association of H-FABP with clinical outcomes in hypertensive patients with aortic valve disease. Echocardiographically determined left ventricular dimensions were signs of cardiac remodelling and correlated significantly with measured levels of H-FABP, whereas Troponin T remained below cut-off levels in all patients [21]. Mirna et al actually reported a significant reduction in H-FABP plasma concentration in 79 patients with severe aortic valve stenosis after conducting transcatheter aortic valve implantation (TAVI), indicating reduced ventricular wall stress and potential reversibility of cardiac remodeling due to valvular replacement [69].…”
Section: H-fabp As a Biomarker In Heart Failurementioning
confidence: 97%
“…In contrast to cardiac troponins, which are bound to the myocyte's structural apparatus, H-FABP is present as soluble protein in the cytoplasm. Therefore, the release into systemic circulation may possibly be detected more rapidly and even after minor myocardial damage [21]. Liebetrau et al, for example, report significantly increased serum levels of H-FABP already 15 minutes after iatrogenic myocardial infarction, caused by transcoronary ablation of septal hypertrophy (TASH).…”
Section: H-fabp As a Biomarker In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical studies, serum H-FABP level is also elevated under heart failure, hypertension, aortic valve regurgitation, renal dysfunction and muscular exercise [17][18][19][20] . Our study demonstrated that H-FABP had a specificity that was slightly lower than CK-MB and cTnT, and was not superior to MYO in any time period within 12 h after onset of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…68 H-FABP levels correlated with relative wall thickness in a cohort of patients with mild to moderate AS and were an independent predictor of cardiac events after adjustment for indices of LV function. 69 …”
Section: Heart-type Cytosolic Fatty Acid Binding Proteins (H-fabp)mentioning
confidence: 99%